SOME ASPECTS OF DIAGNOSTICS AND TREATMENT OF DOG ALOPECIA X - Omelchenko, A.; Аvramenko N.; Volosovets, V.; Volosovets, N.; Gogol, O. (Scientific Progress & Innovations, 2021)
Alopecia X is dog disease of insufficiently studied etiology, characterized by symmetrical, non-itchy and non-inflammatory alopecia that affects the head and distal extremity regions. The main purpose of the work was to study the peculiarities of diagnostics and therapeutic efficacy of different treatment patterns for alopecia X in dogs in the veterinary clinic “Zoovetsentr”, Shostka, Sumy region. The laboratory diagnostic method of trichoscopy was used, which enabled to find changes at hair growth stage. It was planned to solve the following tasks: to study the manifestations and clinical course of alopecia X in a group of small pets; to conduct the comparative evaluation of different diagnostic methods of alopecia X among small pets; study the laboratory methods of alopecia X diagnostics in animals having the symptoms of skin lesions in order to differentiate the diagnosis; to develop treatment measures for alopecia Х. The object of the study were dogs of different breeds and ages with the diagnosis of alopecia X, admitted to the reception and registered in the log of diseased animals. The subject of the study was alopecia X (black skin disease). The data of clinical examinations of animals and the results of laboratory diagnostics have been used in the work. Melatonin (Melatonin, Bioveta) was used orally at a dose of 3−6 mg per dog twice a day for at least 4 months (for dogs ≤ 15 kg – 3 mg, for dogs over 15 kg – 6 mg) as well as microneedle therapy with a dermaroller to restore hair growth in dogs with alopecia X. Trichoscopy of the studied samples revealed the stage of the hair follicle rest (telogen), while the hair root lost pigment, narrowed to the end and took the form of a “spear”. Clinical and biochemical blood tests showed a slight increase in alanine aminotransferase (ALT) (77.4±0.65 IU / l) and urea (13.05±0.37 mmol / l). The therapeutic application of melatonin (Melatonin, Bioveta) partially restored hair growth in 50 % of dogs (6 out of 12), in 20 % the complete recovery of hair after 8 months of therapy was observed, and in 30 % of dogs hair growth did not restore. At the same time, more than 52 % of hair at the anagen stage was detected against the background of treatment measures. The use of dermaroller as a means of microneedle therapy allowed to restore hair growth in 68 cases.